2019
DOI: 10.4081/ejtm.2019.8364
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of renal arterial resistive index in type 2 diabetic nephropathy stage 0-4

Abstract: Chronic kidney disease (CKD) is one of world health problems and its prevalence and incidence is increasing. Chronic Kidney Failure involves a range of pathophysiologic processes that are associated with impaired renal function, leading to cardiovascular morbidity and mortality. Renal artery resistive index (RI) is indicator of atherosclerotic change in small vessels. The current study was aimed to assess RI in diabetic nephropathy patients at stage 0-4 and to compare RRI with HbA1c, systolic blood pressure, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…recently demonstrated that patients with CKD have an increased intrarenal pulsatility and an elevated RRI [ 30 ]. Sistani et al showed significant association between RRI and GFR and albuminuria among 100 patients with diabetic nephropathy [ 31 ]. Bigé et al evaluated RRI levels in 58 patients two days prior to kidney biopsy and found a strong correlation between RRI and interstitial fibrosis as well as accelerated kidney function decline independent of baseline eGFR [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…recently demonstrated that patients with CKD have an increased intrarenal pulsatility and an elevated RRI [ 30 ]. Sistani et al showed significant association between RRI and GFR and albuminuria among 100 patients with diabetic nephropathy [ 31 ]. Bigé et al evaluated RRI levels in 58 patients two days prior to kidney biopsy and found a strong correlation between RRI and interstitial fibrosis as well as accelerated kidney function decline independent of baseline eGFR [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Certain conditions like secondary nephropathies accompanied with glomerular damage, shows RI more than 0.75 to 0.8 because of the co-existing microvascular impairment due to vasculitis, glomerulo/lupus nephritis [ 307 ]. On the other hand, the diabetic nephropathy (DN) with characterized microalbuminuria, hyperfiltration and uncontrolled glycosylated hemoglobin was detected with low RI (∼0.5) and high GFR [ 227 ]. But, in later stages of DN the RI significantly increases due to microvascular injury and reduction in GFR [ 228 ].…”
Section: Research and Development In Ultrasound-based Applications In...mentioning
confidence: 99%